DEVELOPMENT OF SMALL MOLECULE EPIGENETIC THERAPEUTICS FOR INFLAMMATORY BOWEL DISEASE. (21st January 2021) - Li, Yi; Uribe, Gabriela; Pingyuan, Wang; Chen, Haiying; Liu, Zhiqing; Cong, Yingzi; Brasier, Allan; Pinchuk, Irina; Tian, Bing; Zhou, Jia
Abstract: Long-term persistence of chronic inflammation in inflammatory bowel disease (IBD) including ulcerative colitis (UC) and Crohn's disease (CD) is among the major factors contributing to neoplastic transformation and the development of colitis-associated colorectal cancer. There exists a lack of efficient medications for IBD, primarily due to emergence of resistance or side effects. Antibodies against tumor necrosis factor-α (anti-TNFα) are effective therapies in the armamentarium; however, up to 40% of patients become resistant to this therapy. Thus, target-based improved therapy with higher efficacy and enhanced safety profile is urgently needed to fill these gaps. We have demonstrated that bromodomain-containing protein 4 (BRD4), an epigenetic regulator, is required for stabilization of NFkB binding on the promoters of inflammatory genes, activation of RNA polymerase II, and histone H3 Lys122 acetylation (H3K122ac) to permit high levels of inflammatory gene expressions in sentinel immune cells, epithelial cells, and fibroblasts. Our compelling data using human IBD patient samples suggest that BRD4 activation is coincident with the initiation of colonic inflammation. Inhibition of the BRD4 activation is an attractive target for the development of superior therapeutics for IBD, especially for anti-TNFα-resistant patients. We have successfully identified proprietary highly potent and specific BRD4 inhibitors (patent WO 2018/112037 A1) with direct binding modes validated by the solved co-complex crystal structures. We observed that our lead compounds exhibit low toxicity both in vitro and in vivo . Therapeutic administration of our lead inhibitors ZL0516 and ZL0590 significantly reduces mucosal inflammation in several animal models of IBD and restores tissue architecture. Our data show that inhibition of BRD4 results in a decrease of key inflammatory cytokines associated with pathological responses in IBD such as TNFα, IL-6, IL-17A, and IL-1β expression in human colonic epithelial cells and peripheral blood mononuclear cells as well as several animal models of IBD colitis. Collectively, our data suggest that BRD4 activation is critical to the initiation of human colonic inflammation during IBD. BRD4 inhibition disrupts its protein-protein interactions with acetylated histone lysine residues, thereby blocking the pathological activation of the BRD4-NFκB signaling and suppressing colonic inflammation. Thus, BRD4 represents a unique drug target, and novel BRD4 inhibitors ZL0516 and ZL0590 have been identified as promising drug candidates towards the development of small molecule epigenetic therapeutics for the treatment of IBD and its chronic sequelae. Funding support: Crohn's & Colitis Foundation Entrepreneurial Investing (EI) Initiative award, Litwin IBD Pioneers Program, and a research fellowship award from the Crohn's & Colitis Foundation of America.